FINANCIAL FEASIBILITY OF VANNAMEI SHRIMP (Litopenaeus vannamei) FARMING (CASE STUDY: RUPAT UTARA MADANI FOUNDATION) - Aisyah, Siti; Zen, Linda Waty; Tetty, Tetty (Politeknik Kelautan dan Perikanan Dumai, 2025)
The study of the feasibility of vannamei shrimp (Litopenaeus vannamei) aquaculture business is very important to be conducted as an effort to support the establishment of productivee cultivation businesses and provide optimal economic benefits for the local community. The objectives of this study was to assess business income, financial feasibility based on the B/C Ratio, Break Even Point, and Payback Period, as well as sensitivity analysis. The average business income within three years was Rp 422,563,849.The financial viability of the Vannamei shrimp (Litopenaeus vannamei) aquaculture business for three years was calculated, obtaining a B/C Ratio of 0.52, a BEP volume of 13,423 kg,a BEP price of Rp 40,373.11, and a payback period of 6 years and three months.Sensitivity analysis on the increase in the price of production input costs by 10%, obtained a B/C Ratio value of 0.44, a BEP volume 14,165 kg, a BEP price of Rp 42,602 and Payback period of 7 years 1 month.The fluctuating selling price of shrimp, combined with the high death rate of shrimp in the second and third years, rendered this shrimp farming enterprise unprofitable.